THU0643-HPR Prevalence of Foot Problems in People with Inflammatory Arthritis in Singapore. (15th July 2016) - Carter, K.; Lahiri, M.; Cheung, P.; Santosa, A.; Rome, K.
Abstract : Background: Foot problems are highly prevalent in people with inflammatory arthritis [1]. Podiatry intervention can significantly reduce foot pain and disability [2]. Most knowledge of the epidemiology of foot involvement is based on studies from the UK, Europe and New Zealand [1, 3, 4] with limited evidence relating to the podiatric need of people with inflammatory arthritis in Singapore. Objectives: To evaluate the prevalence of foot problems in people with inflammatory arthritis in Singapore. Methods: People with inflammatory arthritis were recruited from the rheumatology outpatient clinic of a large public hospital in Singapore. Disease and clinical characteristics included age, sex, disease duration, BMI, current disease modifying anti-rheumatic drug (DMARD) medications, ESR and CRP. Foot pain was measured using a 10cm visual analogue scale. The Leeds Foot Impact Scale (LFIS) [5] was used to evaluate foot impairment and disability and the Modified Health Assessment Questionnaire (MHAQ) was used to assess global function [6]. Foot assessments were conducted and prevalence of foot deformity was ascertained. Results: We recruited 101 people with inflammatory arthritis, of which 50% were female. The mean of age was 52±15 years, and the mean disease duration was 9.3±0.3 years. The most commonly reported inflammatory arthritis conditions were rheumatoid arthritis (46%), spondyloarthritis (18%) and gout (15%). Most (61%) were overweight with a mean BMI of 27.2±5.4 kg/m 2 . 42% of all participants were on a current prescription of methotrexate and 52% were receiving a combination DMARD therapy. Only 4% were receiving biologic therapy. The mean ESR was 31.6±21.2mg/hr and mean CRP was 27.4±32.2mm/L. The mean of the total LFIS was 17±13 indicating moderate to severe levels of foot impairment and activity limitation. The mean MHAQ score was 0.25±0.36. Over 80% of participants experienced foot problems during the course of their condition, and 48% reported current foot pain. The mean pain score was 5.0±2.3. Despite the high prevalence of foot problems (81%), only 21 participants (21%) had been referred to a podiatrist. Conclusions: This is the first study to investigate the prevalence of foot problems in people with inflammatory arthritis in Singapore. The majority of the participants reported foot problems, but had not been referred to a podiatry service. Findings from this study will be used to improve referral rates, service provision and quality of patient care. References: Grondal L, et al. Acta Orthop. 2008; 79:257–261. Woodburn J, et al. J Rheumatology. 2002; 29:1377–83. Otter S, et al. Clinical Rheumatology. 2010; 29:255–271. Rome K, et al. J Foot Ankle Res. 2009; 2:16. Helliwell P, et al. Arthritis Rheumatology. 2005; 53:418–422. Pincus T, et al. Arthritis Rheumatology. 1983; 26:1346–53. Disclosure of Interest: None declared